Bedeutung der parametrischen und molekularen Bildgebung für das therapeutische Management des Mammakarzinoms - Hack, Carolin; Wetzl, Matthias; Schmidt, Daniela; Beckmann, Matthias (Die Radiologie, 2024)
Background: In recent years, various magnetic resonance (MRI) and positron emission tomography (PET) parameters have been investigated in breast cancer. Parametric imaging focuses on the visualization and quantification of biological, physiological, and pathological processes at the cellular and molecular level. It therefore provides important insights into the key processes in carcinogenesis and tumor progression. This article aims to illustrate the importance for the management of breast cancer. Materials and methods: Based on the current literature, an overview of the current state of parametric breast imaging and its importance in therapy management is given. Moreover, future opportunities and challenges are highlighted. Results: Parametric imaging in breast cancer includes MRI, nuclear medicine procedures such as PET, the combination of different techniques (PET-CT, PET-MRI) and the use of specific radiotracers. Parametric MRI of the breast mainly uses T2 and diffusion-weighted imaging (DWI) as well as dynamic contrast-enhanced MRI (CM-MRI). Quantitative and qualitative imaging biomarkers provide insights into tumor biology and allow conclusions to be drawn about the molecular subtype or prognosis. Conclusions: Recently, parametric imaging has become established in breast diagnostics. It is constantly evolving and will continue to gain in importance in the forthcoming years. It offers the opportunity to improve the diagnosis and treatment management of breast cancer.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Breast neoplasms; Gene expression; Magnetic resonance imaging; Positron emission tomography; Preoperative diagnostics